2020
DOI: 10.2334/josnusd.20-0010
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporter 4 mediates LPS-induced IL-6 production in osteoblasts under high glucose conditions

Abstract: Purpose: Diabetes causes hyperglycemic disorders due to insufficient activity of insulin, and it also increases blood glucose level. Recent studies have reported the relationship between diabetes and periodontal disease. Periodontitis is advanced by inflammatory cytokines stimulated with LPS. The purpose of this study was to investigate the effects of hyperglycemia on the expression of inflammatory cytokines induced by LPS in osteoblasts. Methods: Cells were cultured for 7 and 14 days in the presence or absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Besides, piperine can play an anti-inflammatory role by inhibiting the expression of endothelial cell adhesion molecules that TNF-α induced. [ 54 ] The mechanism involved may be due to the fact that it interferes with the early signal transduction of TNF-α, thereby affecting the activation of nuclear factor kappa-B. Sesamin can significantly reduce IL-6 and IL-1 mRNA expression in human primary synovial fibroblasts, indicating that sesamin can block TNF-α induced pro-inflammatory cytokine mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, piperine can play an anti-inflammatory role by inhibiting the expression of endothelial cell adhesion molecules that TNF-α induced. [ 54 ] The mechanism involved may be due to the fact that it interferes with the early signal transduction of TNF-α, thereby affecting the activation of nuclear factor kappa-B. Sesamin can significantly reduce IL-6 and IL-1 mRNA expression in human primary synovial fibroblasts, indicating that sesamin can block TNF-α induced pro-inflammatory cytokine mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) can stimulate the synthesis and secretion of various pro-inflammatory factors, including IL-6, by binding to TLR and other LPS receptors on cell membranes. [ 54 ] IL-6 is a crucial inflammatory factor in the initial stage of inflammation. Studies have shown that quercetin can reduce inflammation by inhibiting the expression of IL-6mRNA in neutrophils during the process of LPS-induced production of inflammatory cytokine IL-6, thereby decreasing the synthesis and secretion of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Co-stimulation of IL-6 signals ensures a high expression of FOXO1 in LSEC-derived CD8+T cells, which subsequently reduces metabolic activities related to T cell activation [54] , [58] . Conversely, glucose transporter 4 (GLUT4) inhibitor WZB117 is capable of effectively blocking the stimulating effect of glucose on LPS-induced mRNA expression of IL-6, indicating that a high level of blood glucose could stimulate the expression of IL-6 [59] . Notably, the level of circulating IL-6 in patients with type 2 diabetes and/or obesity is 2-3 times as high as that in healthy individuals with normal glucose tolerance [13] , [16] .…”
Section: Role Of Il-6 In Metabolismmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), derived from Gram‐negative bacteria cell wall, is a potent inducer of chemokines and inflammatory cytokines 8 . Previous studies have revealed that the reduction of LPS‐induced proinflammatory cytokines in osteoblasts can inhibit the progression of periodontitis 9 …”
Section: Introductionmentioning
confidence: 99%
“…8 Previous studies have revealed that the reduction of LPSinduced proinflammatory cytokines in osteoblasts can inhibit the progression of periodontitis. 9 Peroxisome proliferator activated receptor-γ (PPAR-γ), which was initially identified as a key regulator of adipocyte differentiation, is also implicated in the regulation of osteoblast differentiation and bone mass. [10][11][12] PPAR-γ also serves as an anti-inflammatory factor in a variety of inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%